Acute Surgical Excision of a Traumatic Fat Fracture in a Professional Soccer Player - Kayani, Babar (J Orthop Case Rep, 2019)
INTRODUCTION: Surgical excision of fat fractures is often reserved for patients with large chronic deformities to improve cosmetic appearance. To our knowledge, the acute surgical management of a traumatic fat fracture has not been previously reported. CASE REPORT: This case report describes the management of a professional soccer player that developed a traumatic fat fracture over the lateral thigh. The patient presented with persistent pain, reduced range of movement, and inability to participate in sporting activity. Symptoms were refractory to non-operative treatment. Following acute surgical excision of the fat fracture, the patient was able to make an early return to sporting activity with no complications at short-term follow-up. CONCLUSION: Acute surgical excision of a traumatic fat fracture may be used as an avenue for improving pain, enhancing functional rehabilitation, and facilitating early return to pre-injury level of function.